Health Counseling About the Danger of Overnutrition and Healthy Menu Simulation For Primary School Children at MIN 7 Jakarta - Lestari, Lilis; Siauta, Jenny Anna; Resi Yesika; Lapepo, Azizah; Hellen Widyawaty; Johana Tapangan; Selvy Oktriana; Tuti Astuti (Rajaki of Tulip Medika Publisher, 2024)
In fact, in DKI Jakarta the prevalence of excess weight in children aged 5-12 years is 15.2% and obesity is 14.0% (2). Nutrition is more a condition of abnormality or excess accumulation of fat in tissue. There are two types of overnutrition problems, namely excess weight and overnutrition. The BMI limit for being categorized as overweight is between 25.1-27.0 kg/m2, while obesity is ≥ 27.0 kg/m2. Elementary school (SD) students are young people who are vulnerable to nutritional problems because children have more varied eating and tastes and want to try various foods and drinks that are high in glucose. Not all elementary schools have a healthy canteen. From the preliminary study that has been carried out, MIN 7 Jakarta has the potential to have more nutrition, with several students found to be in the excess weight category. The aim of this community service activity is to provide education through health promotion to elementary school children about the dangers of overnutrition on their health and future as well as simulating a healthy menu for elementary school children. This community service was carried out at the MIN 7 Jakarta School in the East Cengkareng area, West Jakarta on December 8 and 13 2023. The activity began with carrying out permits, data collection, data analysis, FGD with several stakeholders to determine priority problems for intervention. December 13, by gathering 20 MI 5th grade students, providing education regarding the dangers of overnutrition, a demonstration on making guava juice and providing guava juice and samples of healthy food, then an evaluation was carried out to assess how big the impact of the results of the community service implementation was. Evaluation is carried out by discussion and question and answer. It is hoped that the results of this community service will be used as an alternative ingredient to help fulfill elementary school children's nutrition by using guava fruit as a herbal therapy that can help keep children full for longer.